Recent advances in freshwater crustacean biodiversity and conservation - Kawai, Tadashi; Rogers, D. Christopher (Boca Raton, FL : CRC Press, 2021)
Recent Advances in Freshwater Crustacean Biodiversity and Conservation focuses on minor crustacean groups and regionally endemic groups, all from freshwaters. Chaptersin this book cover crustaceans such as Maxillopods, Mysids, Cumaceans, Isopods, Amphipods, Branchiopods, Copepods, and Decapods. Each looks at global or regional fauna and discusses conservation issues for that group. The majority of the chapters are based on papers presented at symposia organized by the editors at two international scientific meetings held in Barcelona and Washington DC. The contributors are world-renowned experts on their groups, as well as on freshwater crustacean conservation and biodiversity at global levels. It has previously been difficult for conservation managers, NGOs, and university professors and students who may not have access to comprehensive journal subscriptions to find relevant information on diversity and conservation of freshwater crustaceans. This book meets that need, addressing crustacean groups not previously treated and providing additional information beyond any presented in existing books. As the editors write in their introduction: we cannot conserve and we cannot protect what we do not know exists. This is a reliable, cutting-edge reference for anybody involved in crustacean research: students, researchers, agencies, and NGOs, as well as science educators, conservationists, and government conservation policymakers. The book will also be useful for those working in aquaculture and fisheries, given that many of the taxa discussed are economically important.
Campos A New Morphotype of the Crayfish Cambarus hubrichti (Decapoda: Cambaridae) from a Karst Spring Cave System, with Comments on its Ecology by Teresa M. Carroll, D. Christopher Rogers, David B. Stern and Keith A. Crandall Historic Cultural Value of the Japanese Endangered Freshwater Crayfish, Cambaroides Japonicus (De Haan, 1841) (Decapoda: Cambaroididae) by Tadashi Kawai and Jason Coughran Conservation of the Endangered Japanese Crayfish, Cambaroides japonicus (De Haan, 1841) (Decapoda; Cambaroididae) by Tadashi Kawai, Brooke Grubb and Frederic Grandjean General Discussion by Tadashi Kawai and D. Christopher Rogers
OCLC-licensed vendor bibliographic record.
Keywords: Crustacea; Aquatic ecology; Biodiversity conservation; TECHNOLOGY / Agriculture / General; SCIENCE / Life Sciences / Evolution